Thea Stilton and the ice treasure - Stilton, Thea (Scholastic Inc., 2011)
"In this fabumouse adventure, the Thea Sisters head to Alaska, where they're attending a conference held by an important ecological association. Their host and his family are native Alaskans, who show the mouselings their favorite games and activities. But soon there's trouble - the Thea Sisters discover that someone is upsetting the ecosystem by blowing up the ice with explosives! Can the Thea Sisters figure out what's going on and save the day?"